China-Indonesia Maritime Cooperation from the Perspective of Constructivism - Yani, Yang; Machmudi, Yon; Rofii, Muhammad Sya'roni (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2023)
China and Indonesia, as two pivotal nations in Asia, have established a cooperative and mutually beneficial social relationship through their longterm interactions. This relationship transcends the extensive maritime domains and abundant marine resources of both countries, being deeply influenced by their shared norms and collective identities. For instance, China’s 21st Century Maritime Silk Road initiative and Indonesia’s Global Maritime Fulcrum strategy not only exemplify this social relationship but also mirror the mutual understanding and aspirations of both nations regarding maritime cooperation. Specifically, notable advancements have been achieved in areas such as trade, investment, infrastructure development, fisheries, energy, and marine tourism. Concrete examples of these positive outcomes include the collaborative Jakarta-Bandung HighSpeed Rail project and the development of the “Twin Parks” fisheries center between China and Indonesia. However, despite the positive strides in economic cooperation, progress in maritime security collaboration has been comparatively slow. Challenges such as the South China Sea disputes, illegal fishing, Indonesia’s policy of balancing major powers, and the rise of domestic nationalism present potential hurdles to cooperation. To further deepen their partnership, both countries need to continually adjust and reshape their norms and identities through interaction, enhance political trust, and strengthen cultural exchanges. Moreover, actively exploring possibilities in non-traditional security cooperation, such as joint efforts in marine environmental protection and combating maritime crime, could pave new pathways for the development of their bilateral relations.